Effectiveness of The BYOND Application in Gold Installment Transactions at Bank Syariah Indonesia: Phenomenological Study - Elisa Tri Rahayu; Dony Burhan Noor Hasan (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This study aims to determine the effectiveness of the BYOND by BSI application in supporting gold installment transactions at Bank Syariah Indonesia based on user experience. The approach used is a qualitative descriptive phenomenology (Husserlian) transcendental approach involving several informants, consisting of active customers and employees of Bank Syariah Indonesia KCP Lamongan, selected through purposive sampling techniques until data saturation is reached. Data were collected through in-depth semi-structured interviews and analyzed using NVivo 14 through thematic coding techniques based on the stages of Moustakas and Colaizzi. The results show that the application's effectiveness is determined by three main pillars: technological ease, sharia compliance, and user experience quality. This third pillar contributes significantly to customer trust and loyalty, in line with the Technology Acceptance Model (TAM), which contradicts the Sharia compliance dimension. Identified obstacles include network disruptions, limited gold stock, OTP errors, and low digital literacy in understanding digital sharia contracts. This research contributes to the development of Islamic fintech literature by offering a three-pillar model as a framework for evaluating the effectiveness of digital Islamic banking applications, while also providing strengthening of technological infrastructure and sustainable Islamic education programs.